Health insurance status of cross-border migrant children and the associated factors: a study in a Thai-Myanmar border area - Chalermpol Chamchan; Kanya Apipornchaisakul (BMC, 2022)
Abstract Background Although policies of Thailand for migrant health protection are inclusive for all migrant groups, due to existing constraints in practices and policy implementation, many migrant children still lack the protection. This study aimed to assess the health insurance status of children aged 0-14 whose parents were cross-border migrant workers in Thailand, and factors related to the status. Methods A Thai-Myanmar border area, being developed as a 'special economic zone' by the Thai government, was selected as a study site. With a cross-sectional research design, the study collected primary data in late 2018 by a structured questionnaire from 402 migrant households that contained 803 children. The logistic generalized estimating equation (GEE) technique was applied to examine factors associated with the children's health insurance status. These included socio-economic factors, migration factors, and health insurance-related factors. Results It is found that 83.2% of the migrant children did not have health insurance. Factors associated with the health insurance status included age 12-14 years (Odds ratio (OR) 2.34; 95% confidence interval (CI) 1.23-4.46), having a birth certificate (OR 1.89, 95% CI 1.04-3.45), and plan of the family in the future to remain the child in Thailand (OR 2.37, 95% CI 1.09-5.17). The primary carer's factors that were important health insurance-related factors included having no legal work permit (OR 4.12, 95% CI 1.88-9.06), having health insurance (OR 8.51, 95% CI 3.93-18.41), little or no ability to communicate in Thai (OR 0.31, 95% CI 0.14-0.66), and understanding the right of migrant children to purchase health insurance (OR 2.57, 95% CI 1.52-4.34). Conclusions The findings point to the need for every migrant child to have a birth certificate, diminishing language barriers, and providing education and motivation about the need for health insurance for migrants and their accompanying dependents, especially children. For further studies, it is suggested to include migrant health insurance supply-side factors with qualitative analyses to understand how all the factors interactively determine the health insurance status of migrant children.